A cysteine and a hydrophobic sequence in the noncleaved portion of the pre-C leader peptide determine the biophysical properties of the secretory core protein (HBe protein) of human hepatitis B virus. - Wasenauer, G (J Virol, 1992)
The molecular basis of the biophysical and antigenic differences between the cellular core protein (HBc protein) and the secreted core protein (HBe protein) of human hepatitis B virus was examined. The data show that the properties which distinguish the HBe protein from the HBc protein are due mostly to the 10-amino-acid portion of the HBe leader sequence which remains attached to the HBe protein after cleavage. A cysteine located within this region determines the quaternary structure and the antigenicity of the HBe protein. If this cysteine is lacking, the HBe protein, which is predominantly a monomer with only HBe antigenicity, is expressed as a disulfide-linked homodimer showing both HBe and HBc antigenicity. However, dimerization of the HBe protein was found to be neither sufficient nor required for particle formation. In fact, aggregation of the HBe protein was found to be inhibited by the strongly hydrophobic tripeptide Trp-Leu-Trp, which is also located in the noncleaved portion of the signal sequence. If this tripeptide was converted into either Asp-Asn-Asn or Ala-Asp-Leu, the HBe protein assembled into particles, independent of the presence of the cysteine. IMAGES: